2015
DOI: 10.1016/j.chb.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial impacts of engaging in Second Life for individuals with physical disabilities

Abstract: a b s t r a c tThe psychological experiences associated with engagement in virtual worlds have been well documented in the existing literature. The current study aimed to explore the motivations, experiences and psychosocial impacts of engaging in the virtual world ''Second Life''. This aimed to extend previous findings by specifically exploring the phenomenological experiences within a sample of individuals with physical disabilities. This was achieved by conducting in-world interviews with five participants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In addition, social media platforms such as Discord or Twitch can be used to facilitate communication while playing videogames online ( 23 ). Duchenaunt and More reported that videogames could be used as a method for social participation, and Kleban and Kaye stated that it can be seen as a tool to increase social networks ( 24 , 25 ). Interacting with others through videogames thus has the potential to have a positive impact on mental health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, social media platforms such as Discord or Twitch can be used to facilitate communication while playing videogames online ( 23 ). Duchenaunt and More reported that videogames could be used as a method for social participation, and Kleban and Kaye stated that it can be seen as a tool to increase social networks ( 24 , 25 ). Interacting with others through videogames thus has the potential to have a positive impact on mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of online videogames has been described as a valuable technical aid in enabling social participation in situations where physical gatherings are challenging ( 26 ). People living with disabilities have emphasized that within a virtual world, their physical disability is not visible ( 25 ).…”
Section: Introductionmentioning
confidence: 99%